Biogeochemical and ecological variability during the late summer–early autumn transition at an ice‐floe drift station in the Central Arctic Ocean. Issue Volume 66:Issue S1(2021) Supplement (21st December 2020) - Schanke, Nicole L.; Bolinesi, Francesco; Mangoni, Olga; Katlein, Christian; Anhaus, Philipp; Hoppmann, Mario; Lee, Peter A.; DiTullio, Giacomo R.
Abstract: As the annual expanse of Arctic summer ice‐cover steadily decreases, concomitant biogeochemical and ecological changes in this region are likely to occur. Because the Central Arctic Ocean is often nutrient and light limited, it is essential to understand how environmental changes will affect productivity, phytoplankton species composition, and ensuing changes in biogeochemistry in the region. During the transition from late summer to early autumn, water column sampling of various biogeochemical parameters was conducted along an ice‐floe drift station near the North Pole. Our results show that as the upper water column stratification weakened during the late summer–early autumn transition, nutrient concentrations, particulate dimethylsulfoniopropionate (DMSPp ) levels, photosynthetic efficiency, and biological productivity, as estimated by ΔO2 /Ar ratios, all decreased. Chemotaxonomic (CHEMTAX) analysis of phytoplankton pigments revealed a taxonomically diverse picoautotrophic community, with chlorophyll (Chl) c 3 ‐containing flagellates and the prasinophyte, Pyramimonas spp., as the most abundant groups, comprising ~ 30% and 20% of the total Chl a (TChl a ) biomass, respectively. In contrast to previous studies, the picoprasinophyte, Micromonas spp., represented only 5% to 10% of the TChl a biomass. Of the nine taxonomic groups identified, DMSPp was most closely associated with Pyramimonas spp., a Chl b ‐containing species not usually considered a high DMSP producer. As the extent and duration of open, ice‐free waters in the Central Arctic Ocean progressively increases, we suggest that enhanced light transmission could potentially expand the ecological niche of Pyramimonas spp. in the region.